Comparing soil-to-plant cadmium (Cd) transfer and potential human intake among rice cultivars with different Cd tolerance levels grown in a tropical contaminated soil - Nogueira, Thiago Assis Rodrigues [UNESP]; Muraoka, Takashi; Silveira, Laís Karina; da Silva, Jamile Santos; Abreu-Junior, Cassio Hamilton; Lavres, José; Martinelli, Adriana Pinheiro; Teixeira Filho, Marcelo Carvalho Minhoto [UNESP]; He, Zhenli; Jani, Arun Dilipkumar; Ganga, Antonio; Capra, Gian Franco (Springer Nature, 2022)
With its accumulation in upland rice, cadmium (Cd) can easily enter the human food chain, which poses a global health threat considering nearly half of the human population depends on rice as a staple food source. A study was conducted to (1) evaluate Cd accumulation by rice cultivars, grown in Cd-polluted Tropical Oxisols, with different levels of Cd tolerance; (2) quantify Cd transfer from soil to rice shoots and grain; and (3) estimate daily Cd intake by humans. Three rice cultivars, characterized by low (Cateto Seda–CS), medium (BRSMG Talento–BT), and high (BRSMG Caravera–BC) Cd uptake capacity, were investigated. Rice cultivars were exposed to increasing soil Cd concentrations (0.0, 0.7, 1.3, 3.9, 7.8, and 11.7 mg kg−1). Analysis was performed on soil, shoots, and grain. Shoot biomass and grain yield decreased with increasing Cd supply, suggesting the following Cd tolerance: CS > BT > BC. Cadmium concentrations in shoots and grain increased when exposed to Cd. Only CS did not exceed the maximum Cd limit permitted in food (0.40 mg kg−1), when rates up to 1.3 mg kg−1 of Cd were applied to soil. Considering daily rice consumption levels in Brazil, Cd intake often exceeds maximum tolerable levels. Continuous monitoring of soil Cd concentrations is a pivotal step in avoiding hazards to humans. Such monitoring is important on a global scale since outside of Asia, Brazil is the leading rice-producing and rice-consuming country. Graphical abstract: [Figure not available: see fulltext.]
Keywords: Daily intake; Food safety; Oryza sativa L; Plant nutrition; Soil pollution